Diphenoxylate hydrochloride and atropine sulfate overdose in an infant presenting as respiratory failure - Sanchari Ghosh; Saurabh Sutradhar; Prabhas Prasun Giri (Wolters Kluwer Medknow Publications, 2021)
A fixed-dose combination of diphenoxylate hydrochloride and atropine sulfate marketed widely as oral tablets, is one of the most frivolously used drugs to treat diarrhea in adults. Its safety and efficacy in children younger than 2 years are not known. In this case, we came across a 45-day-old infant being maltreated with adult dose of the drug, for diarrhea, by a local charlatan, which landed him in the emergency room with lethargy, altered sensorium, and type 2 respiratory failure and ultimately had to be salvaged by mechanical ventilation. This case describes the life-threatening adverse effects of an adult drug on the pediatric age group.